Aspek Hukum Penggunaan Force Intercept Dalam Insiden Udara Militer (Studi Kasus Respons F-16 TNI AU terhadap Pesawat F-18 US Navy di Bawean) - Tambunan, Daniel (Media Hukum Indonesia (MHI), 2025)
Aircraft interception is an action taken by a country's military aircraft to identify and escort foreign aircraft that enter its airspace without permission, in accordance with the provisions of the 1944 Chicago Convention and Law No. 1/2009 on Aviation. This article discusses the regulations related to interception and the actions taken by the Indonesian Air Force (TNI AU) in handling airspace violations over Bawean Island by the United States' F-18 aircraft. The discussion in this article emphasizes that interception functions as a law enforcement measure against airspace violations, with procedures that must comply with the provisions in Annex 2 of the Chicago Convention. The Bawean tragedy serves as a concrete example of the application of interception in Indonesia, highlighting the importance of airspace surveillance to safeguard the security and sovereignty of the nation